2019
DOI: 10.3389/fneur.2019.01178
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Comparisons of the Hippocampal Changes in the Transient and Permanent Middle Cerebral Artery Occlusion Rat Models

Abstract: Ischemic strokes are categorized by permanent or transient obstruction of blood flow, which impedes delivery of oxygen and essential nutrients to brain. In the last decade, the therapeutic window for tPA has increased from 3 to 5–6 h, and a new technique, involving the mechanical removal of the clot (endovascular thrombectomy) to allow reperfusion of the injured area, is being used more often. This last therapeutic approach can be done until 24 h after stroke onset. Due to this fact, more acute ischemic stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 70 publications
1
39
0
Order By: Relevance
“…In the BCAO group, the cerebral blood flow presents a sharp decline leading to acute ischemic impairment in cerebral microcirculation, acute cerebral ischemic infarction, and high mortality rates (Naritomi, 1991) regardless of compensation via vertebral arteries and collateral circulation that typically contributes to CBF recovery (Kato et al, 2019). Thus, we deduce that BCAO rats are more akin to models of acute focal cerebral ischemia caused by middle cerebral artery occlusion (Naritomi, 1991;Shah et al, 2019). This may explain the differences in FA value changes between the BCAS and BCAO models.…”
Section: Discussionmentioning
confidence: 91%
“…In the BCAO group, the cerebral blood flow presents a sharp decline leading to acute ischemic impairment in cerebral microcirculation, acute cerebral ischemic infarction, and high mortality rates (Naritomi, 1991) regardless of compensation via vertebral arteries and collateral circulation that typically contributes to CBF recovery (Kato et al, 2019). Thus, we deduce that BCAO rats are more akin to models of acute focal cerebral ischemia caused by middle cerebral artery occlusion (Naritomi, 1991;Shah et al, 2019). This may explain the differences in FA value changes between the BCAS and BCAO models.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, role of the JNK pathway in inflammatory cascades and cellular death has been strongly established ( Ali A et al, 2020 ), and ROS and inflammatory cytokines can trigger JNK activation ( Ali A et al, 2020 ; Ali T et al, 2020 ; Ling et al, 2020 ). Furthermore, the p-JNK pathway has been implicated in various animal models and human diseases ( Shah et al, 2018 ; Li and Liu, 2019 ; Ali A et al, 2020 ; Ling et al, 2020 ; Malik et al, 2020 ), and the downregulation or inhibition of this pathway has been found to contribute to the protective strategy ( Shah et al, 2019 ). We observed similar activities in the APAP-intoxicated group, and carveol significantly reduced p-JNK expression.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining was performed as previously described with minor modifications (Shah et al, 2019c;Iqbal et al, 2020). The slides were processed for the antigen retrieval step (enzymatic method), then washed with PBS.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%